Peningkatan Kemampuan Menghafal Mufrodat Melalui Pendekatan Berdiferensiasi Berbantuan Media Pada Pembelajaran Bahasa Arab di Kelas III Madratsah Ibtidaiyyah Salamah Kota Jambi - Rengganis Diladias; Andi Nurhasanah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to determine the effectiveness of the media-assisted differentiation method in improving the ability to memorize Arabic vocabulary in grade III students of MI Salamah. The background of this study is based on the phenomenon of low student ability in memorizing vocabulary due to teaching techniques that tend to be monotonous and repetitive, thus less motivating students to learn actively. This study uses the Classroom Action Research (CAR) approach referring to the John Elliot model, which is implemented in two cycles, each including the planning, action implementation, observation, and reflection stages. The subjects of the study were 26 grade III students. Data were collected through oral examinations, interviews, and observations of teaching and learning activities. The results of the study showed a significant increase in students' ability to memorize vocabulary after the application of the media-assisted differentiation method. In Cycle I, the average percentage of student and teacher activity achievement was 72%, with only 61.54% of students being able to reach the memory test passing standard. After the strategy improvement in Cycle II, the average student and teacher activity increased to 90%, while the percentage of students reaching the memory test passing standard jumped to 92.30%. This improvement demonstrates that the differentiation method, which utilizes learning media, provides more varied, engaging stimuli, and is tailored to each student's learning characteristics. The conclusion of this study is that the media-assisted differentiation method is effective in improving elementary school students' memorization of Arabic vocabulary. The implication of this finding is the importance of teachers implementing creative, adaptive, and media-based learning approaches to optimize Arabic language learning outcomes, particularly vocabulary mastery.